HYDRO-ABRASIVE JET CLEANING TECHNOLOGY OF STEEL SHEETS DESIGNED FOR LASER CUTTING - I. V. Kachanov; A. V. Filipchik; A. M. Sheiko; A. A. Roubchenya; S. I. Ushev (Наука и техника)
Investigations executed by the BNTU “Shipbuilding and hydraulics” department have shown that rather efficient implementation of the requirements to the metal sheet surface designed for laser cutting can be achieved by using hydro-abrasive jet cleaning while applying water pump equipment with the range of pressure – 20–40 MPa. Type of working fluid plays a significant role for obtaining surface of the required quality. The conducted experiments have demonstrated that the efficient solution of the assigned problems can be ensured by using a working fluid containing bentonite clay, surface-active agent polyacrylamide, soda ash and the rest water.